More Reflections On The Nasal Classes In Bantu - Hyman, Larry (My University, 2018)
Although long considered to be a Bantu innovation, Miehe (1991) proposed that the nasal consonants present in Bantu noun classes 1, 3, 4, 6, 9 and 10 should be reconstructed in pre-Proto-Bantu, even possibly at the Proto-Niger-Congo stage. Since there has been no comprehensive response to Miehe, the two of us organized a workshop to look at the question in more detail. In this paper I update the problem from Hyman (1980b) and Miehe (1991), expanding the coverage and considering various scenarios that could have led to innovation (or loss). While there have been three hypothetical reconstructions (nasal consonants, nasalized vowels, no nasal consonants), we have not yet arrived at a “solution” that answers the relevant questions discussed in this paper.
Keywords: Bantu; nasal classes; hypothetical reconstructions